The stability region of the Streptomyces lividans plasmid pIJ101 encodes a DNA-binding protein recognizing a highly conserved short palindromic sequence motif - Thoma, Lina; Sepulveda, Edgardo; Latus, Annette; Muth, Günther (Frontiers in Microbiology, 2014)
Conjugation is a driving force in the evolution and shaping of bacterial genomes. In antibiotic producing streptomycetes even small plasmids replicating via the rolling-circle mechanism are conjugative. Although they encode only genes involved in replication and transfer, the molecular function of most plasmid encoded proteins is unknown. In this work we show that the conjugative plasmid pIJ101 encodes an overlooked protein, SpdA2. We show that SpdA2 is a DNA binding protein which specifically recognizes a palindromic DNA sequence (sps). sps is localized within the spdA2 coding region and highly conserved in many Streptomyces plasmids. Elimination of the palindrome or deletion of spdA2 in plasmid pIJ303 did not interfere with conjugative plasmid transfer or pock formation, but affected segregational stability.